Health: Constitutional Right of a programmatic and operational nature - Quijano Caballero, Oscar Ítalo (2016)
The right to health is a universal right of second-generation, classified in the setof social, economic and cultural rights of mankind; gaining acceptance worldwide for its programmatic nature. On the verge of reaching 100 years of that recognition, its character of constitutionally recognized, operational, enforceable or subjective right has been consolidated thanks to the development of the jurisprudence of the constitutional courts; subsequent to this legal phenomenon, its enforceability trough protective process of amparo in the constitutional code of procedure is regulated in our country and expands its protection, in both areas, the powers assigned to the regulatory and supervisory body of the health sector at the national level, of administrative sanctioning power.